2007
DOI: 10.1002/app.26296
|View full text |Cite
|
Sign up to set email alerts
|

Effect of zinc oxide nanoparticles as cure activator on the properties of natural rubber and nitrile rubber

Abstract: Zinc oxide (ZnO) nanoparticles were synthesized by homogeneous precipitation and calcination method and were then characterized by transmission electron microscopy and X-ray diffraction analysis. Synthesized ZnO was found to have no impurity and had a dimension ranging from 30-70 nm with an average of 50 nm. The effect of these ZnO nanoparticles as cure activator was studied for the first time in natural rubber (NR) and nitrile rubber (NBR) and compared with conventional rubber grade ZnO with special reference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
98
0
2

Year Published

2010
2010
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 160 publications
(102 citation statements)
references
References 37 publications
(26 reference statements)
2
98
0
2
Order By: Relevance
“…2(b-d)]. The SEM images of NZ 5 and NZ 7 [ Fig. 2(b,c)] show only very few agglomerates, which are micro particles of CBS.…”
Section: Cure Properties Of Mixesmentioning
confidence: 87%
See 3 more Smart Citations
“…2(b-d)]. The SEM images of NZ 5 and NZ 7 [ Fig. 2(b,c)] show only very few agglomerates, which are micro particles of CBS.…”
Section: Cure Properties Of Mixesmentioning
confidence: 87%
“…Tensile strength increased with increase in dosage of ZOBS up to 7 phr in the mix NZ 5 (Table III). This was due to increase in the number of sulfidic crosslinks by the enhanced synergic action between BIAT caps on zinc oxide surface and the CBS particles diffusing on to ZnO.…”
Section: Tensile Propertiesmentioning
confidence: 88%
See 2 more Smart Citations
“…This effect can be partly attributed to the small particle size of the Zn 1Àx Mg x O particles. Bhowmick and coworkers 4,5 found that ZnO nanoparticles (30-70 nm) increased the crosslink degree by 15% compared with standard ZnO. On the other hand, the fact that, even with bigger sizes, higher amounts of crosslinked products are formed suggests that Zn 1Àx Mg x O nanoparticles are more active and more effective transporting sulfur into the hydrocarbon chain than ZnO nanoparticles.…”
Section: Zn 12x Mg X O Nanoparticles As New Activators For Vulcanizationmentioning
confidence: 93%